Super-early-strength anticorrosive mortar and preparation method thereof

By using a combination formula of anticorrosion resin, plasticizer and solid waste powder in building anticorrosion mortar, the existing anticorrosion cement mortar has solved the problem of poor acid resistance and slow development of strength, and achieved high impermeability, toughness and volume Stability extends the service life of the building.

CN119241130APending Publication Date: 2025-01-03HUBEI UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411324129.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-23
Publication Date
2025-01-03

AI Technical Summary

Technical Problem

The existing anti-corrosion cement mortar has poor acid resistance and slow strength development, making it difficult to use in high-temperature, high humidity, high acid and alkali or high salt environments for a long time.

Method used

The ultra-premature anticorrosion mortar formula consisting of anticorrosion resin, plasticizer, defoaming agent, hydrophobic agent, solid waste powder, tailings sand and toughening fibers is used to utilize the resin through the combination of thermoplastic resin and chlorinated polypropylene resin. Film-forming properties and high acid resistance, form cured bodies with high permeability, high toughness and high adhesion, and improve strength and volume stability through solid waste powder and tailings sand.

Benefits of technology

It has achieved super early strength mortar curing, reaching 10MPa compressive strength within 20 minutes and 50MPa in one day. It has high toughness, crack resistance and good volume stability, seepage resistance and corrosion resistance, extending the life of the engineering building .

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005054910630000071
    Figure BDA0005054910630000071
  • Figure BDA0005054910630000081
    Figure BDA0005054910630000081
Patent Text Reader

Abstract

The invention discloses super-early-strength anticorrosive mortar and a preparation method thereof. The super early strength anticorrosive mortar is prepared from the following components in parts by weight: 400 to 500 parts of anticorrosive resin, 40 to 50 parts of plasticizer, 1 to 5 parts of defoaming agent, 25 to 35 parts of water repellent, 200 to 300 parts of solid waste micro powder, 200 to 300 parts of tailing sand, 100 to 150 parts of exciting agent, 5 to 10 parts of toughening fiber and 150 to 200 parts of water. According to the invention, the thermoplastic anticorrosive resin and the solid waste-based alkali-activated material are adopted as main cementing materials, so that the coating has the characteristics of short curing time, high early strength, acid and alkali corrosion resistance, water and oil corrosion resistance, high toughness and crack resistance, and is suitable for various corrosive environments; meanwhile, the solid waste is subjected to resource utilization, so that the cost is reduced, and secondary utilization of solid waste resources is facilitated.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of building engineering materials, and in particular to an ultra-early strength anticorrosive mortar and a preparation method thereof. Background Art

[0002] The application of building anti-corrosion materials in water conservancy projects, marine projects, subway projects, tunnel projects, chemical industry projects and complex environment projects in the west plays an important role in extending the life of engineering buildings. The quality of the performance of building anti-corrosion materials directly affects the safety and service life of the project. Existing building anti-corrosion can be solved by painting or anti-corrosion coatings on the buildings, but in some harsh environments with high temperature, high humidity, high acidity and alkali or high salt, the usual anti-corrosion coatings are difficult to meet the requirements of consistency with the life of the project due to their poor durability; the existing anti-corrosion cement mortar has defects such as poor acid resistance and slow strength development, and the materials used are mostly high-quality resources. Using treated solid waste as raw materials to produce synchronous grouting materials can solve the problem of shortage of high-quality resources. Summary of the invention

[0003] In view of this, the present invention aims to provide an ultra-early strength anti-corrosion mortar to solve the problems of poor acid resistance and slow strength development of existing anti-corrosion cement mortar.

[0004] To achieve the above object, the technical solution of the present invention is achieved as follows:

[0005] A super early strength anticorrosive mortar comprises the following components by weight: 400-500 parts of anticorrosive resin, 40-50 parts of plasticizer, 1-5 parts of defoamer, 25-35 parts of water repellent, 200-300 parts of solid waste micropowder, 200-300 parts of tailings sand, 100-150 parts of activator, 5-10 parts of toughening fiber and 150-200 parts of water.

[0006] Optionally, the anti-corrosion resin is perchlorethylene resin and chlorinated polypropylene resin.

[0007] The present invention adopts thermoplastic anticorrosive resin to ensure that the cooling process is synchronized with the curing process, which is conducive to the rapid development of strength. At the same time, the film-forming and gelling properties of the resin cooling process are utilized to form a solidified body with high impermeability, high toughness and high adhesion, ensuring the performance of various properties of the mortar. At the same time, the high acid resistance, salt water resistance and aging resistance of vinyl chloride resin and chlorinated polypropylene resin are utilized to ensure the durability and long life of the anticorrosive mortar.

[0008] Optionally, the mass ratio of the perchlorethylene resin to the chlorinated polypropylene resin is 1:(1-4).

[0009] Optionally, the chlorine content of the perchlorethylene resin is 65%.

[0010] Optionally, the molecular weight of the chlorinated polypropylene resin is 60,000-80,000.

[0011] Optionally, the plasticizer is one of phthalate and terephthalate.

[0012] The plasticizer of the invention has excellent adaptability and compatibility with perchlorethylene resin and chlorinated polypropylene resin, weakens the secondary bonds between resin molecules, increases the mobility of resin molecular bonds, reduces the crystallinity of resin molecules, increases the plasticity of resin molecules, and enhances their flexibility.

[0013] Optionally, the defoaming agent is one of a silicone defoaming agent and a polyether defoaming agent.

[0014] Optionally, the water repellent is calcium stearate powder.

[0015] The present invention utilizes the hydrophobic property of calcium stearate and combines the film-forming effect of resin to ensure that the mortar is not easily corroded by water, thereby improving the water resistance and anti-penetration property of the mortar.

[0016] Optionally, the specific surface area of ​​the calcium stearate powder is 350 m 2 / kg~450m 2 / kg.

[0017] Optionally, the solid waste powder is a mixture of blast furnace slag, steel slag, non-ferrous metal slag and fly ash in any proportion. Among them, non-ferrous metal slag is metallurgical slag other than steel smelting slag, mainly including copper, nickel, zinc and rare metal smelting slag.

[0018] The solid waste micropowder of the present invention contains amorphous active silicon-aluminum components, which form a hardened body under the stimulation of sodium silicate and sodium hydroxide, further providing a cementing body for the anti-corrosion mortar to ensure the development of strength; at the same time, the alkali-stimulated solid waste material has little volume deformation during the hardening process, which is also beneficial to further improve the volume stability of the product.

[0019] Optionally, the specific surface area of ​​the solid waste powder is 600m 2 / kg~800m 2 / kg.

[0020] Optionally, the tailings sand is one of iron tailings, copper tailings and gold tailings.

[0021] Optionally, the particle size of the tailings sand is ≤1.18 mm.

[0022] Optionally, the tailings sand is obtained by sequentially undergoing screening, washing and drying processes.

[0023] Optionally, the activator is a mixture of water glass and sodium hydroxide.

[0024] Optionally, the mass ratio of water glass to sodium hydroxide is 9:1.

[0025] Optionally, the modulus of the water glass is 2 and the solid content is 50%.

[0026] Optionally, the toughening fiber is basalt fiber.

[0027] Optionally, the length of the basalt fiber is 9 mm.

[0028] The present invention utilizes the low surface energy of basalt fiber to increase the effective contact area between the fiber and the resin film and the hardened binder, thereby increasing the friction and grip therebetween. When there is a large bending stress, it can also play a better bridging role, thereby achieving the purpose of toughening and preventing cracking.

[0029] The second object of the present invention is to provide a method for preparing the above-mentioned ultra-early strength anticorrosive mortar, the preparation method comprising the following steps:

[0030] 1) heating the anticorrosive resin until it is melted, then adding the plasticizer and the defoamer, stirring while adding, and after mixing evenly, adding the water repellent, stirring while adding, and mixing evenly to obtain slurry A;

[0031] 2) mixing the activator and the water, adding the solid waste powder while stirring, and after the mixture is evenly mixed, adding the tailings sand and the toughening fiber, stirring while adding, and mixing evenly to obtain slurry B;

[0032] 3) Add the slurry B into the slurry A and mix them to obtain an ultra-early strength anti-corrosion mortar.

[0033] Compared with the prior art, the ultra-early strength anticorrosive mortar of the present invention has the following advantages:

[0034] 1. The ultra-early strength anti-corrosion mortar prepared by the present invention has the characteristics of fast curing and high early strength. The slurry begins to harden when it cools down, and the curing time can be controlled within 20 minutes to prevent the mortar from sagging. The 2h compressive strength can reach more than 10MPa, and the 1d compressive strength can reach more than 50MPa. It has high bonding strength, and the bonding strength with the substrate can reach more than 2MPa.

[0035] 2. The ultra-early strength anti-corrosion mortar obtained by the present invention has a compression-to-bend ratio of less than 2, a compressive elastic modulus of not more than 20 MPa, and has high toughness and anti-cracking performance. It also has good volume stability, impermeability, and erosion resistance. The volume linear change rate is less than 0.01%, and the water seepage pressure is greater than 2 MPa. After immersion in acid, alkali, salt solutions, water, and oil, there is no peeling or cracking on the surface. The corrosion resistance coefficient is greater than 95%, and the service life can be guaranteed under complex conditions.

[0036] 3. The main raw materials used in the present invention are industrial solid waste such as solid waste powder and tailings. The solid waste is recycled, which saves resources and reduces costs. It is an environmentally friendly material and is conducive to promoting the secondary utilization of solid waste resources. DETAILED DESCRIPTION

[0037] In order to enable those skilled in the art to better understand the technical solutions and technical effects of the present invention, several embodiments are provided below. Obviously, what is described below is only an embodiment and does not limit the protection scope of the present invention.

[0038] Example 1

[0039] A method for preparing an ultra-early strength anticorrosive mortar specifically comprises the following steps:

[0040] 1) Weigh the raw materials according to the proportion, and the raw materials and their amounts include: 400kg of anticorrosive resin (200kg of perchlorethylene resin, 200kg of chlorinated polypropylene resin), 40kg of plasticizer (40kg of phthalate), 1kg of defoamer (1kg of silicone defoamer), 25kg of water repellent (calcium stearate powder), 300kg of solid waste powder (100kg of blast furnace slag powder, 50kg of steel slag powder, 50kg of non-ferrous metal slag powder, 100kg of fly ash), 300kg of iron tailings, 150kg of activator (135kg of water glass, 15kg of sodium hydroxide), 5kg of toughening fiber (basalt fiber), and 200kg of water;

[0041] 2) Add the weighed anticorrosive resin into a kettle, heat until the resin is melted, add a plasticizer and a defoamer, stir while adding, mix evenly, then add a water repellent, stir while adding, mix evenly, to obtain slurry A;

[0042] 3) Add the activator and water into a mixer, add the solid waste powder while stirring, mix evenly, then add the tailings sand and toughening fiber, stir while adding, mix evenly, and obtain slurry B;

[0043] 4) Add the slurry B into the slurry A and mix to obtain an ultra-early strength anti-corrosion mortar, wherein the obtained ultra-early strength anti-corrosion mortar can be used within 10 minutes.

[0044] In this embodiment, the chlorine content of the perchlorethylene resin is 65%; the molecular weight of the chlorinated polypropylene resin is 65,000; the specific surface area of ​​the calcium stearate powder is 415 m 2 / kg; the specific surface area of ​​solid waste powder is 730m 2 / kg; the tailings sand is obtained by screening, washing and drying processes in sequence, and the particle size of the tailings sand is ≤1.18mm; the modulus of water glass is 2, and the solid content is 50%; the length of the basalt fiber is 9mm.

[0045] Example 2

[0046] The difference between this embodiment and embodiment 1 is that the raw material composition of the ultra-early strength anti-corrosion mortar of this embodiment is: 420kg of anti-corrosion resin (180kg of perchlorethylene resin, 240kg of chlorinated polypropylene resin), 42kg of plasticizer (42kg of phthalate), 2kg of defoamer (2kg of silicone defoamer), 28kg of water repellent (calcium stearate powder), 280kg of solid waste powder (80kg of blast furnace slag powder, 70kg of steel slag powder, 60kg of non-ferrous metal slag powder, 70kg of fly ash), 270kg of iron tailings, 140kg of activator (126kg of water glass, 14kg of sodium hydroxide), 6kg of toughening fiber (basalt fiber), and 185kg of water.

[0047] The other steps are the same as those in Example 1.

[0048] Example 3

[0049] The difference between this embodiment and embodiment 1 is that the raw material composition of the ultra-early strength anti-corrosion mortar of this embodiment is: 450kg of anti-corrosion resin (150kg of perchlorethylene resin, 300kg of chlorinated polypropylene resin), 45kg of plasticizer (45kg of terephthalate), 3kg of defoamer (3kg of silicone defoamer), 30kg of water repellent (calcium stearate powder), 240kg of solid waste powder (50kg of blast furnace slag powder, 100kg of steel slag powder, 40kg of non-ferrous metal slag powder, 50kg of fly ash), 250kg of copper tailings, 130kg of activator (117kg of water glass, 13kg of sodium hydroxide), 7kg of toughening fiber (basalt fiber), and 175kg of water.

[0050] The other steps are the same as those in Example 1.

[0051] Example 4

[0052] The difference between this embodiment and embodiment 1 is that the raw material composition of the ultra-early strength anti-corrosion mortar of this embodiment is: 480kg of anti-corrosion resin (120kg of perchlorethylene resin, 360kg of chlorinated polypropylene resin), 48kg of plasticizer (48kg of terephthalate), 4kg of defoamer (4kg of polyether defoamer), 32kg of water repellent (calcium stearate powder), 220kg of solid waste powder (20kg of blast furnace slag powder, 150kg of steel slag powder, 20kg of non-ferrous metal slag powder, 30kg of fly ash), 230kg of copper tailings, 120kg of activator (108kg of water glass, 12kg of sodium hydroxide), 8.5kg of toughening fiber (basalt fiber), and 165kg of water.

[0053] The other steps are the same as those in Example 1.

[0054] Example 5

[0055] The difference between this embodiment and embodiment 1 is that the raw material composition of the ultra-early strength anti-corrosion mortar of this embodiment is: 500kg of anti-corrosion resin (100kg of perchlorethylene resin, 400kg of chlorinated polypropylene resin), 50kg of plasticizer (50kg of terephthalate), 5kg of defoamer (5kg of polyether defoamer), 35kg of water repellent (calcium stearate powder), 200kg of solid waste powder (50kg of blast furnace slag powder, 50kg of steel slag powder, 50kg of non-ferrous metal slag powder, 50kg of fly ash), 200kg of copper tailings, 100kg of activator (90kg of water glass, 10kg of sodium hydroxide), 10kg of toughening fiber (basalt fiber), and 150kg of water.

[0056] The other steps are the same as those in Example 1.

[0057] Comparative Example 1

[0058] An anticorrosive mortar is prepared by the following method:

[0059] Weigh the raw materials, which include: 400 kg bisphenol A epoxy resin, 60 kg aliphatic diamine curing agent, 200 kg P˙O42.5 cement, 200 kg sand with a particle size not greater than 1.18 mm, and 80 kg water; put the bisphenol A epoxy resin into a mixer, add water, cement and sand while stirring, stir evenly, then add the aliphatic diamine curing agent, stir evenly, and use.

[0060] Comparative Example 2

[0061] An anticorrosive mortar is prepared by the following method:

[0062] Weigh the raw materials, which include: 400 kg bisphenol A epoxy resin, 60 kg aliphatic diamine curing agent, 200 kg solid waste powder (50 kg blast furnace slag powder, 50 kg steel slag powder, 50 kg non-ferrous metal slag powder, 50 kg fly ash), 200 kg copper tailings, 100 kg activator (90 kg water glass, 10 kg sodium hydroxide), 10 kg toughening fiber (basalt fiber), and 150 kg water; put the bisphenol A epoxy resin into a blender, add water, solid waste powder and copper tailings, activator and toughening fiber while stirring, stir evenly, then add the aliphatic diamine curing agent, stir evenly, and use.

[0063] Comparative Example 3

[0064] An anticorrosive mortar is prepared by the following method:

[0065] 1) Weigh the raw materials, including: 500kg anticorrosive resin (100kg perchlorethylene resin, 400kg chlorinated polypropylene resin), 50kg plasticizer (50kg terephthalate), 5kg defoamer (5kg polyether defoamer), 35kg water repellent (calcium stearate powder), 200kg P˙O42.5 cement, 200kg sand with a particle size not greater than 1.18mm, and 80kg water.

[0066] 2) Add the weighed anticorrosive resin into a kettle, heat until the resin is melted, add a plasticizer and a defoamer, stir while adding, mix evenly, then add a water repellent, stir while adding, mix evenly, to obtain slurry A;

[0067] 3) Put cement and water into a mixer, add sand while stirring, mix well, and obtain slurry B;

[0068] 4) Add the slurry B into the slurry A and mix to obtain an anti-corrosion mortar.

[0069] The mortars obtained in Examples 1-5 and Comparative Examples 1-3 were tested for properties such as curing time, compressive strength, flexural strength, bonding strength, elastic modulus, volume stability, impermeability and immersion in corrosive liquid. The results are shown in Table 1.

[0070] As can be seen from Table 1, the various properties of the ultra-early-strength anticorrosive mortars obtained in Examples 1-5 of the present invention are better than those of the ordinary resin mortars in Comparative Example 1, showing superior early-strength performance, anticorrosion performance, toughness and volume stability compared to ordinary resin mortars; relative to Example 5 of the present invention, Comparative Example 2 uses ordinary epoxy resin and the solid waste-based powder material of the present invention to prepare the anticorrosive mortar, and Comparative Example 3 uses ordinary cement-based materials and the anticorrosive resin of the present invention to prepare the anticorrosive mortar, both of which extend the curing time of the obtained anticorrosive mortar, and reduce the early and late mechanical properties, anticorrosive performance and volume stability. In particular, Comparative Example 2 has a significant reduction, while Example 5 uses the solid waste-based powder material of the present invention and the anticorrosive resin to prepare the anticorrosive mortar, and the two work together to produce a "1+1>2" effect for various properties, especially the early strength, oil resistance and acid-base salt solution corrosion resistance.

[0071] Table 1 Test results of mortar properties obtained from Examples 1-5 and Comparative Examples 1-3

[0072]

[0073]

[0074] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. An ultra-early strength anticorrosive mortar, characterized in that: The invention comprises the following components by weight: 400-500 parts of anticorrosive resin, 40-50 parts of plasticizer, 1-5 parts of defoaming agent, 25-35 parts of water repellent, 200-300 parts of solid waste powder, 200-300 parts of tailings sand, 100-150 parts of activator, 5-10 parts of toughening fiber and 150-200 parts of water.

2. The ultra-early strength anticorrosive mortar according to claim 1, characterized in that: The anticorrosive resin is a mixture of perchlorethylene resin and chlorinated polypropylene resin in a mass ratio of 1:(1-4).

3. The ultra-early strength anticorrosive mortar according to claim 1, characterized in that: The plasticizer is one of phthalate and terephthalate.

4. The ultra-early strength anticorrosive mortar according to claim 1, characterized in that: The defoamer is one of an organosilicon defoamer and a polyether defoamer.

5. The ultra-early strength anticorrosive mortar according to claim 1, characterized in that: The water repellent is calcium stearate powder.

6. The ultra-early strength anticorrosive mortar according to claim 1, characterized in that: The solid waste powder is a mixture of blast furnace slag, steel slag, non-ferrous metal slag and fly ash in any proportion.

7. The ultra-early strength anticorrosive mortar according to claim 1, characterized in that: The tailings sand is one of iron tailings, copper tailings and gold tailings.

8. The ultra-early strength anticorrosive mortar according to claim 1, characterized in that: The activator is a mixture of water glass and sodium hydroxide in a mass ratio of 9:

1.

9. The ultra-early strength anticorrosive mortar according to claim 1, characterized in that: The toughening fiber is basalt fiber.

10. A method for preparing the ultra-early strength anticorrosive mortar according to any one of claims 1 to 9, characterized in that: The following steps are involved: 1) heating the anticorrosive resin until it is melted, then adding the plasticizer and the defoamer, stirring while adding, and after mixing evenly, adding the water repellent, stirring while adding, and mixing evenly to obtain slurry A; 2) mixing the activator and the water, adding the solid waste powder while stirring, and after the mixture is evenly mixed, adding the tailings sand and the toughening fiber, stirring while adding, and mixing evenly to obtain slurry B; 3) Add the slurry B into the slurry A and mix them to obtain an ultra-early strength anti-corrosion mortar.